A cross-brain neural mechanism for human-to-human verbal communication. Issue 9 (3rd September 2018) - Hirsch, Joy; Adam Noah, J; Zhang, Xian; Dravida, Swethasri; Ono, Yumie
Abstract: Neural mechanisms that mediate dynamic social interactions remain understudied despite their evolutionary significance. The interactive brain hypothesis proposes that interactive social cues are processed by dedicated brain substrates and provides a general theoretical framework for investigating the underlying neural mechanisms of social interaction. We test the specific case of this hypothesis proposing that canonical language areas are upregulated and dynamically coupled across brains during social interactions based on talking and listening. Functional near-infrared spectroscopy (fNIRS) was employed to acquire simultaneous deoxyhemoglobin (deOxyHb) signals of the brain on partners who alternated between speaking and listening while doing an Object Naming & Description task with and without interaction in a natural setting. Comparison of interactive and non-interactive conditions confirmed an increase in neural activity associated with Wernicke's area including the superior temporal gyrus (STG) during interaction ( P = 0.04). However, the hypothesis was not supported for Broca's area. Cross-brain coherence determined by wavelet analyses of signals originating from the STG and the subcentral area was greater during interaction than non-interaction ( P < 0.01). In support of the interactive brain hypothesis these findings suggest a dynamically coupled cross-brain neural mechanism dedicated to pathways that share interpersonal information.